El Sistema Interdisciplinario PALT Da Respuesta A La Formación De Emprendedores - Radano, Eduardo; Velinsone, Daniel (European Scientific Journal, ESJ, 2016)
This paper aims to use the PALT tool to guide the training of entrepreneurs, determining the content that should have such training. In order to ensure that this tool met that purpose we used the results of the survey of entrepreneurs in the second course the entrepreneurial training program, conducted with the logistical support and coordination, of the Center for Entrepreneurship of the University of Flores, in the 2nd. Semester of 2015. The tool PALT, developed by Dr. Roberto Kertész in his Manual of Family Business (summarizing a course / workshop in 1992), it proposes an interdisciplinary model of organizational diagnosis and intervention. It is a management proposal for owners of family businesses and also for those who advise them, based on this model. The comparison between it and the results of the survey allowed us to check: 1. First, the adequacy of the model as a reference for training content for entrepreneurs. 2. Then, a pool of ideas about what might be the said contents, related to the management of the enterprises. 3. Emergents regarding some omissions, to be covered in future trainings. 4. The inclusion of interdisciplinarity in practice, not only from academics, whose synthesis is more concrete action on the ground. The first match for the above, is a starting point for future actions regarding: 1. More information surveys. 2. Improvements in the courses and workshops that we conduct from the Center for Entrepreneurship. In those cases, the courses we produce as designers and teachers.